Influencing the Decision to Use Factors BCA QR-ku - Suherman, Winda; Sari, Indana Zulfa; Krisdina, Tiana Fenny (LPPM Universitas Sebelas April, 2025)
This study investigates the factors influencing the adoption of the QR-KU BCA menu, utilizing a modified Technology Acceptance Model (TAM) framework to analyze public perception of this new BCA feature. The research employs multiple linear regression, processing data collected via a Likert-scale questionnaire to examine the relationship between variables and usage intention. The findings reveal that Perceived Usefulness (PU) and Trust significantly affect Behavioral Intention to Use the QR-KU BCA service. This underscores the importance of clear perceived benefits and user confidence as primary drivers for the adoption of this digital payment service. These results offer strategic recommendations for BCA: focus on improving utility value and strengthening user trust to encourage wider feature adoption